Centimeter-Level Positioning Using an Efficient New Baseband Mixing and Despreading Method for Software GNSS Receivers. (22nd October 2007) - Petovello Petovello, M. G. M. G.; Lachapelle Lachapelle, G. G.
Abstract : This paper presents an efficient new method for performing the baseband mixing and despreading operations in a software-based GNSS receiver, and demonstrates that the method is capable of providing measurements for centimeter-level positioning accuracy. The method uses a single frequency carrier replica for the baseband mixing process, enabling all satellites to perform mixing simultaneously and yielding considerable computational savings. To compensate for signal-to-noise ratio (SNR) losses caused by using a single frequency carrier replica, the integration interval after despreading is divided into subintervals, and the output from each subinterval then compensated for the known frequency error. Using this approach, receiver processing times are shown to be reduced by approximately 21% relative to the next fastest method when tracking seven satellites. The paper shows the mathematical derivation of the new algorithm, discusses practical considerations, and demonstrates its performance using simulations and real data. Results show that the new method is able to generate pseudorange and carrier phase measurements with the same accuracy as traditional methods. Stand-alone positioning accuracy is at the meter level, while differential processing can produce fixed ambiguity carrier phase positions accurate to the centimeter level.